An expert committee model to estimate lines of code. - Aggarwal, K. K. (Software engineering notes.)
Resource Estimation is a challenging activity, in the early stages of project development. Once the functionality desired by the user is ascertained, function points can be calculated. This paper proposes to estimate Lines of Code once the Function Point count is known, using linear regression techniques and also a neural network model. These two are then combined to propose an expert committee model which gives better results. This is validated by empirical data available from ISBSG data set (release 9).